Recent advancements in CRISPR/Cas technology for accelerated crop improvement - Das, Debajit; Singha, Dhanawantari L.; Paswan, Ricky Raj; Chowdhury, Naimisha; Sharma, Monica; Reddy, Palakolanu Sudhakar; Chikkaputtaiah, Channakeshavaiah (Planta, 2022)
Main conclusion Precise genome engineering approaches could be perceived as a second paradigm for targeted trait improvement in crop plants, with the potential to overcome the constraints imposed by conventional CRISPR/Cas technology . The likelihood of reduced agricultural production due to highly turbulent climatic conditions increases as the global population expands. The second paradigm of stress-resilient crops with enhanced tolerance and increased productivity against various stresses is paramount to support global production and consumption equilibrium. Although traditional breeding approaches have substantially increased crop production and yield, effective strategies are anticipated to restore crop productivity even further in meeting the world’s increasing food demands. CRISPR/Cas, which originated in prokaryotes, has surfaced as a coveted genome editing tool in recent decades, reshaping plant molecular biology in unprecedented ways and paving the way for engineering stress-tolerant crops. CRISPR/Cas is distinguished by its efficiency, high target specificity, and modularity, enables precise genetic modification of crop plants, allowing for the creation of allelic variations in the germplasm and the development of novel and more productive agricultural practices. Additionally, a slew of advanced biotechnologies premised on the CRISPR/Cas methodologies have augmented fundamental research and plant synthetic biology toolkits. Here, we describe gene editing tools, including CRISPR/Cas and its imitative tools, such as base and prime editing, multiplex genome editing, chromosome engineering followed by their implications in crop genetic improvement. Further, we comprehensively discuss the latest developments of CRISPR/Cas technology including CRISPR-mediated gene drive, tissue-specific genome editing, dCas9 mediated epigenetic modification and programmed self-elimination of transgenes in plants. Finally, we highlight the applicability and scope of advanced CRISPR-based techniques in crop genetic improvement.